Jawabanmu

Jawaban paling cerdas!
2014-02-26T22:55:39+07:00
F(x) = x+2
y = x+2
x = y-2
 f^{-1} (y) = y-2
 f^{-1} (x) = x-2

g(x) =  \frac{1}{x}
y =  \frac{1}{x}
xy = 1
x =  \frac{1}{y}
 f^{-1} (x) =  \frac{1}{x}


a.  (fog)^{-1}  (x) = ( g^{-1} o f^{-1} ) (x) =  g^{-1} ( f^{-1}  (x)) =  g^{-1} (x-2) =  \frac{1}{x-2}
c.  (fog)^{-1}  (4) =  \frac{1}{4-2}  \frac{1}{2}

b.  (gof)^{-1}  (x) =  ( f^{-1} o g^{-1} ) (x) =  f^{-1} ( g^{-1} (x)) =  f^{-1} ( \frac{1}{x} ) =  \frac{1}{x} - 2 =  \frac{1-2x}{x}
d.  (gof)^{-1}  (4) =  \frac{1-2(4)}{4} - \frac{7}{4}